2022
DOI: 10.1002/eco.2427
|View full text |Cite
|
Sign up to set email alerts
|

Flow behaviour in a multi‐layered vegetated floodplain region of a compound channel

Abstract: Riparian vegetation plays a crucial role in determining the flow behaviour in the channel. The effect of flow on the slope and main channel varies based on the size, type, and density of floodplain vegetation in a compound channel. Though real field vegetation distribution is non‐uniform, most studies mainly concentrate on uniformly distributed vegetation with fixed vegetation height. This paper attempts to address this issue through laboratory studies as it was not explored properly. Flow properties like velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…These two turbulent shear components, which are operating in opposite streamwise and transverse directions on the plane of sediments, are τZX and τZY, respectively. The streamwise Reynolds shear stress distribution τZX=ρ()uw¯ (Barman & Kumar, 2022a; Pu, 2021) in the riverbank segment is given in Figure 6. Figure 7 illustrates the riverbank's transverse Reynolds shear stress contours where u ′ and w ′ are obtained from the experimental readings using ADV, as mentioned in Section 2.2 above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These two turbulent shear components, which are operating in opposite streamwise and transverse directions on the plane of sediments, are τZX and τZY, respectively. The streamwise Reynolds shear stress distribution τZX=ρ()uw¯ (Barman & Kumar, 2022a; Pu, 2021) in the riverbank segment is given in Figure 6. Figure 7 illustrates the riverbank's transverse Reynolds shear stress contours where u ′ and w ′ are obtained from the experimental readings using ADV, as mentioned in Section 2.2 above.…”
Section: Resultsmentioning
confidence: 99%
“…It was sowed as multiple seeds were placed in a straight‐line hole and watered, as shown in Figure 2(b). Such straight lines were placed at a distance of 9 cm to get sparse vegetation density based on the literature (J. Barman & Kumar, 2022a, 2022b; Mossa et al, 2017; Zong & Nepf, 2010). The vegetation was supported for 15 days when they achieved a height of 0.3 m. It was now double the height of the riverbank and could be used as flexible emergent vegetation, as shown in Figure 2(d,e).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations concentrate mainly on the hydraulics of different forms of vegetation. Different materials have been used to imitate aquatic vegetation such as rods and wooden cylindrical dowels for rigid vegetation (Cheng & Nguyen, 2011; Panigrahi & Khatua, 2015; Sharil et al, 2016) with uniform arrays of staggered or aligned (Chatelain & Proust, 2021; Dupuis et al, 2016; Martino et al, 2012) or randomly (Ricardo et al, 2014; Tanino & Nepf, 2008) or partially vegetated open channel (Buckman, 2013; Devi et al, 2019; White & Nepf, 2008) or multi‐layer vegetation (Barman & Kumar, 2022; Liu et al, 2010), flexible vegetation like blades or strips (Chen et al, 2011; Nepf & Vivoni, 2000), natural vegetation (Carollo et al, 2005; Devi et al, 2017; Stephan & Gutknecht, 2002), combined layer of flexible vegetation in emergent and submerged condition (Li et al, 2014), and various combinations (Freeman et al, 2000; Järvelä, 2002). In comparison with studies related to flexible vegetation types, there have been more studies in channels with rigid vegetation (Wilson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the effort of the secondary flow is significant in the redistribution of longitudinal momentum in the compound open channel flows. Barman and Kumar [17] physically collected the turbulent measurements in the heterogeneous canopy within the floodplain area of compound open channels. The differences of flow properties were identified, compared to the cases with homogeneous floodplain vegetation.…”
Section: Introductionmentioning
confidence: 99%